FEATURES AND COMPONENTS OF THE PARENTS AND EDUCATORS' PSYCHOLOGICAL READINESS TO INTEGRATE WITH CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Mariia Ivanivna OLIINYK; Roksolyana Vasylivna OLIINYK (Association of Social and Educational Innovation, 2021)
The article studies the main problematic aspects of the preschool teachers and parents' psychological readiness to inclusive education of preschool children. It is known that inclusive education creates new demands to all participants of the educational and training process in pre-school educational establishments, including parents. Preschool educators are characterized by an inadequate formation level of such readiness components for inclusion as: cognitive and emotional. It should also be noted that attitudes towards children with special educational needs are also linked to stereotypes that have already emerged, especially in relation to those children who have a more difficult form of inclusion. The problem is that the implementation of inclusive education shows a difference in understanding and expectation of the tasks facing both parents and teachers.